2008
DOI: 10.1021/la702848x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Gold Nanobelts and Nanocombs in Aqueous Mixed Surfactant Solutions

Abstract: Well-defined gold nanobelts as well as unique gold nanocombs made of nanobelts were readily synthesized by the reduction of HAuCl4 with ascorbic acid in aqueous mixed solutions of the cationic surfactant cetyltrimethylammonium bromide (CTAB) and the anionic surfactant sodium dodecylsulfonate (SDSn). Single-crystalline gold nanobelts grown along the <110> and <211> directions were prepared in mixed CTAB-SDSn solutions at 4 and 27 degrees C, respectively. Furthermore, single-crystalline gold nanocombs consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
161
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(171 citation statements)
references
References 67 publications
4
161
2
4
Order By: Relevance
“…Gold is generally considered as an inert metal toward methanol oxidation, [30][31][32] but an advantage of gold as catalyst is that the poisoning intermediates are not formed, and recent studies [6,7,[9][10][11][30][31][32] discovered that Au could exhibit an unusually high electrocatalytic activity. The electrocatalytic activity was attributed to the size and shape and the initial results showed that gold could be a promising candidate for the electrocatalytic oxidation of methanol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold is generally considered as an inert metal toward methanol oxidation, [30][31][32] but an advantage of gold as catalyst is that the poisoning intermediates are not formed, and recent studies [6,7,[9][10][11][30][31][32] discovered that Au could exhibit an unusually high electrocatalytic activity. The electrocatalytic activity was attributed to the size and shape and the initial results showed that gold could be a promising candidate for the electrocatalytic oxidation of methanol.…”
Section: Introductionmentioning
confidence: 99%
“…Although the size effect has been extensively studied, [8] the influence of surface structure of nanostrutures as electrocatalysts is still in the focus of investigations. [9][10][11] Different crystal surfaces or directions may exhibit different physical and chemical properties due to the anisotropic properties of crystals. For example, the {111}, {110} and {100} surfaces of a face-centred cubic (fcc) metal, such as gold, show differences not only in the surface atom density, but also in the electronic structures and the resulting chemical reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Au nanoplates were sandwiched by the protecting agent and then grew into a network structure 47,48 . This edge formation can be explained by the limited supply of the precursor only at the edges.…”
Section: Aggregation On Templatesmentioning
confidence: 99%
“…Однако матричный синтез имеет ряд недостатков, в частности, необходимость удаления матрицы, сложность масштабирования получения нанопроводов для последующего коммерческого использования [6]. В связи с этим активно развиваются химические методы синтеза одномерных наноструктур на основе металлов и их производных [10,11]. Одномерные наноструктуры на поверхности электродов получают, используя адсорбцию наночастиц на поверхности одномерных структур [12,13].…”
unclassified